Using artificial intelligence to predict the success of therapeutic dental treatment - Vatamanіuk Nataliya; Dubchak Bohdan (Scientific Research and Experimental Development, 2025)
Today, artificial intelligence (AI) is becoming increasingly common in medicine, as well as dentistry. Neural networks are a part of AI that are similar to the human brain in their work and can solve problems and make decisions quickly [1]. The main component of any neural network is an artificial neuron, which is designed and created on the principles of a human neuron. By assembling and combining artificial neurons and connecting all of them using mathematical operations, a network is created that solves a specific task (analysis of X-ray images, etc.) [2].